Large shareholders, board independence, and minority shareholder rights: Evidence from Europe - Kim, Kenneth A.; Kitsabunnarat-Chatjuthamard, P.; Nofsinger, John R. (Journal of Corporate Finance, 2007)
We examine the relation between minority shareholder protection laws, ownership concentration, and board independence. Minority shareholder rights is a country-level governance variable. Ownership structure and board composition represent firm-level governance variables. Prior research hypothesizes and documents a negative relation between countries' minority shareholder rights quality and firms' ownership concentration. We introduce the hypothesis that shareholder protection rights and firms' board independence are positively related. When a country's minority shareholder rights are strong, then minority shareholders should have the legal power to affect board composition. Using a sample of large firms from 14 European countries, we test both hypotheses and find that countries with stronger shareholder protection rights have firms with lower ownership concentrations and with more independent directors, consistent with both hypotheses. We also find evidence that ownership concentration and board independence are negatively related.